Ventricular arrhythmia storm in the era of implantable cardioverter-defibrillator. Issue 1079 (26th August 2015) - Looi, Khang-Li; Tang, Anthony; Agarwal, Sharad
ABSTRACT: In the era of widespread use of implantable cardioverter-defibrillators (ICDs) for both primary and secondary prevention of sudden cardiac death, a significant proportion of patients experience episodes of multiple ventricular tachycardia/fibrillation over a short period of time requiring device interventions. The episodes are termed ventricular arrhythmia (VA) or electrical storms. VA storm is a tragic experience for patients, with many psychological consequences. Current management for VA storms remains complex. Acutely, administration of β-blockers, amiodarone and sedation or intubation is generally required to suppress sympathetic tone. Interventional treatment includes catheter ablation and sympathetic blockade by left cardiac sympathetic denervation. Strategies to modify autonomic tone to suppress VAs are the rationale of various novel interventions that have been published in recent studies. All patients with VA storm should be considered for transfer to an experienced high-volume tertiary centre for evaluation and treatment to prevent further recurrence of VA storm.